SISTEM PENUNJANG KEPUTUSAN DENGAN METODE AHP MENENTUKAN PERINGKAT SISWA BERDASARKAN HARD SKILL DAN SOFT SKILL - Haris Munandar; Tumini . (Jurnal informasi dan komputer, 2022)
On determining student's rank, class teachers are faced for giving information or reporting their student'srank. The difficulty that they have is to determine student's rank in a short time while there are large numberof students. Based on that situation, class teachers need a system which could help them for determiningstudent's rank. The problem in this research is how to make decision supporting system using analyticalhierarchy process (ahp) method for determining student's rank. This research is purposed to get informationwhether the application of Decision Supporting System using analytical hierarchy process is valid and beable to help for determining student's rank. The purpose of this research is be able to make DecisionSupporting System for determining student's rank. The validity of this application could be tested and be ableto help class teachers to determine their student's rank. The method which used to develop this system isresearch and development method. The research is done in SMK Industri Jababeka